THEORETICAL AND PRACTICAL ASPECTS OF INTRODUCING INNOVATIONS IN THE ENTERPRISE'S MARKETING ACTIVITY - Liudmyla Sokolova; Ganna Veriasova; Maryna Zinchenko (Сучасний стан наукових досліджень та технологій в промисловості, 2020)
The subject of this study is a new direction in the marketing activities of the enterprise - neuromarketing, which uses the latest developments in the field of psychology, neurobiology and behavioral economics in the analysis of consumer behavior. The goal of the study is to determine the definition of "neuromarketing", provide a comparative analysis of traditional marketing and neuromarketing, to identify strengths and weaknesses, opportunities and threats of neuromarketing, and create a new information component of the system for scanning strategic information of business entities of the country. Further development of certain theoretical and practical aspects of the use of neuromarketing as an effective modern toolkit for product promotion in commodity markets has been studied. The following tasks are solved in the article: analysis of the theoretical and practical aspects of the use of neuromarketing, analysis of the main methods for obtaining and processing relevant information. The following methods are used: theoretical generalization, comparative analysis, analytical, analysis and synthesis, SWOT analysis. The following results were obtained: descriptive model of neuromarketing was proposed; the principles of neuromarketing were formulated; the comparison of neuromarketing and traditional marketing was done; the main ethical problems of neuromarketing research were considered; the SWOT-analysis of neuromarketing, which will contribute to a clearer understanding of the nature was carried out, advantages and disadvantages of the new innovative marketing technology were studied, assessment of the prospects for the development of neuromarketing in the country was considered; proposals for the further development of the marketing information system of the enterprise by supplementing its primary information obtained in the process of applying neuromarketing – an innovative marketing technology were developed. Conclusions: It has been established that neuromarketing is an innovative modern instrument of traditional marketing, a promising method of product promotion. A study of neuromarketing has shown that this area today is one of the marketing technologies of the future; the functionality of it has not yet been fully formed and explored. However, today neuromarketing is a powerful innovative marketing tool that, over the quarter century of its existence, has made a significant contribution to both the development of business structures and the science of traditional marketing.